Phenomenological model and working mechanism of bio-inspired polymeric composites driven by water gradient. Issue 1 (4th January 2016) - Lu, Haibao; Zhang, Aying; Yao, Yongtao; Lin, Long
Abstract : Purpose: – This paper aims to present a phenomenological model to investigate the underlying mechanism and predict the bio-inspired performance under different thermo-temporal conditions. Design/methodology/approach: – Flory-Rehner free-energy functions are applied to quantitatively identify the driving forces in the viscously bio-inspired response of a dynamic polymer network. Furthermore, the permeation transition equation is adopted to couple water gradient and water sorption/desorption into the free-energy function. Findings: – The results show that the influence of potential energy on deformation can be related to a stretching ratio that uniquely determines water sorption/desorption, locomotion frequency and contractile stress. Finally, by means of combining the free-energy function and Arrhenius equation, a phenomenological thermo-temporal model is developed and verified by the experimental results. Research limitations/implications: – This study focuses on exploring the theoretical mechanism and significantly enhances understanding of relevant experimental features reported previously. Originality/value: – The outcome of this study will provide a powerful phenomenological and quantitative tool for study on shape memory effect in bio-inspired polymers.